2014
DOI: 10.1371/journal.pone.0113443
|View full text |Cite
|
Sign up to set email alerts
|

Oleoyl-Lysophosphatidylcholine Limits Endothelial Nitric Oxide Bioavailability by Induction of Reactive Oxygen Species

Abstract: Previously we reported modulation of endothelial prostacyclin and interleukin-8 production, cyclooxygenase-2 expression and vasorelaxation by oleoyl- lysophosphatidylcholine (LPC 18:1). In the present study, we examined the impact of this LPC on nitric oxide (NO) bioavailability in vascular endothelial EA.hy926 cells. Basal NO formation in these cells was decreased by LPC 18:1. This was accompanied with a partial disruption of the active endothelial nitric oxide synthase (eNOS)- dimer, leading to eNOS uncoupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 58 publications
(85 reference statements)
0
16
0
7
Order By: Relevance
“…The above event is related to the induction of ROS over-production by LPC. Recently oleoyl-LPC has been shown to cause a decrease of NO production, and eNOS uncoupling, but increase of ROS production in EAHY endothelial cells [ 13 ]. Peng et al (2010) also found the inhibition of NO, stimulation of ROS by LPC to stimulate caspase 3-dependent apoptotic response in endothelial cells [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above event is related to the induction of ROS over-production by LPC. Recently oleoyl-LPC has been shown to cause a decrease of NO production, and eNOS uncoupling, but increase of ROS production in EAHY endothelial cells [ 13 ]. Peng et al (2010) also found the inhibition of NO, stimulation of ROS by LPC to stimulate caspase 3-dependent apoptotic response in endothelial cells [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wire myography was done as previously described [20]. Briefly, mouse aortic rings 2 mm in length were isolated and positioned in small wire myograph chambers (Danish MyoTechnology, Aarhus, Denmark) containing physiological salt solution (PSS) (114 mM NaCl, 4.7 mM KCl, 0.8 mM KH 2 PO 4 , 1.2 mM MgCl 2 , 2.5 mM CaCl 2 , 25 mM NaHCO 3 and 11 mM d -glucose pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…EA.hy 926 cells were plated (250,000 cells/well) onto 6 well plates. After 24 h, confluent cells were treated with 100 μg/mL EV-HDL or EL-HDL in DMEM without FCS for 5 or 16 h. Intracellular conversion of L- [ 3 H]arginine into L-[ 3 H]citrulline was measured as previously described [ 17 ]. Briefly, after incubation with EV-HDL or EL-HDL, cells were washed and incubated at 37 °C with 50 mmol/L Tris buffer, pH 7.4, containing 100 mmol/L NaCl, 5 mmol/L KCl, 1 mmol/L MgCl 2 , 3 mmol/L CaCl 2 , 5% (vol/vol) FCS, and L-[2,3- 3 H]arginine (~106 dpm) in the absence or presence of 0.5 μmol/L calcium iono- phore A23187.…”
Section: Methodsmentioning
confidence: 99%
“…Next, the rings were contracted with increasing concentrations of norepinephrine (NE) (1 nmol/L – 0.3 μmol/L) (Sigma-Aldrich) to produce 80% of the maximum contraction achieved by modified PSS followed by endothelium-dependent relaxation to cumulatively increasing concentrations of acetylcholine chloride (1 nmol/L – 0.3 μmol/L) (Sigma- Aldrich). After washout and equilibration, the rings were constricted with one dose of NE in the presence or absence of L-NNA (300 μmol/L) to 80% of the maximal constriction achieved by modified PSS [ 17 ]. Thereafter, 100 μg/mL EV-HDL protein or EL-HDL protein were added to the rings in the absence or presence of L-NNA (300 μmol/L).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation